Differences in the Biomechanics of the Vertical Jumps in Young Adult Handball Players: Effect of the Countermovement and the Arm Swing - V. Panoutsakopoulos; M.C. Kotzamanidou; A.K. Giannakos (Editura Universitatii Transilvania din Brasov, 2022)
The purpose of the study was to examine the sex and jump test effect on the biomechanics of vertical jump performance in young adult handball players. Nineteen men and 19 women handball players were tested in the squat jump (SQJ) and the countermovement jump with (CMJF) and without (CMJ) an arm swing. Results indicated a significant (p < .05) sex and jump test main effect on jump height and power output. Also, a significand (p < .05) sex, jump test and sex-jump test interaction was revealed for impulse time, time to achieve maximum force and work output. No sex differences (p > .05) were observed for the jump height increment when using a countermovement and an arm swing. The differences found suggest that sex-specific training should be applied to optimize jumping ability in young adult handball players.